Change in southern right whale breathing behavior in response to gull attacks - Fazio, Ana (2014)
Animals may develop behavioral responses to avoid discomforting situations. In particular, pain can result in learned avoidance behaviors. We report such a case in southern right whales (Eubalaena australis) that have been the target of attacks by kelp gulls (Larus dominicanus) that feed on their skin and blubber in the surrounded waters of Península Valdés, Chubut (Argentina) since the 1980s. The increase in the attacks over the years triggered on whales the development of alternative postures to keep their backs protected from the gulls. Recently, a particular avoidance behavior has been observed, the “oblique breathing,” in which whales breathe with only the head out of the water. The main goal of this work is to describe the emergence of oblique breathing in two areas of Golfo Nuevo (P. Valdés) which have high number of whales and gull attacks, during the whale reproductive seasons in 2010, 2012 and 2013. Results suggest that all age and sex classes of whales can breathe obliquely. Emergence of the oblique breathing seems to have proceeded in three stages: (1) the origin, with rare observations, (2) the spread, when the behavior was registered only during gull attacks and (3) the establishment, when whales performed it in a preventive manner, even when attacks were not occurring. Oblique breathing is likely to pose extra energy costs, which could be detrimental to whales, especially for recently born calves. However, given the increasing prevalence of this behavior, it seems to be a useful strategy to prevent harassment by gulls.